(SOCIAL) MEDIA USE AND NEWS: NEWS USAGE PATTERNS AND THEIR EFFECTS ON POLITICAL PARTICIPATORY BEHAVIOR - Kümpel Anna Sophie; Karnowski, Veronika (AoIR Selected Papers of Internet Research, 2015)
Mass media use is a crucial determinant of political participatory behavior, which is true both for “traditional” news media as well as for online media. For example, studies have shown a positive relationship between reading newspapers or television news use and political efficacy and engagement (e.g. Eveland & Scheufele, 2000; Moeller, de Vreese, Esser, & Kunz, 2014; Norris, 1996; Zhang & Chia, 2006). However, critical voices have argued that media use provokes political distrust and cynicism and thus ultimately leads to decreased participatory behavior (e.g. McBride, 1998; Putnam, 1995). In the context of online media and the simultaneous utopian and dystopian imaginaries of the internet for civic engagement, the debate about the impact of news media use on political participation and efficacy continues. While some authors emphasize the adverse effects (e.g. Kraut et al., 1998), latest studies find positive effects of online news use in general as well as of social media news use in particular (e.g. Bode, Vraga, Borah, & Shah, 2014; Esser & de Vreese, 2007; Gil de Zúñiga, Jung, & Valenzuela, 2012). Just recently, Boulianne (2015) conducted a meta-analysis of research on social media use and participation and found more than 80% of the coefficients to be positive, indicating a positive relationship between social media use and participation in civic and political life. Our goal is to study the relationship between general news use and political participatory behavior more thoroughly and to investigate the effects of different news usage patterns. We define political participatory behavior as online and offline forms of political participation that, for example, include discussing political issues, commenting political news on social networking sites (SNS) or participating in petitions. Since we assume that device use is associated with specific information needs (e.g. Humphreys, von Pape, & Karnowski, 2013), we not only focused on participants’ use of different media for learning and obtaining further information about news events but also on the devices (e.g. TV, laptop, smartphone) that are used for these tasks.